The University of Nicosia student intranet and its interface evaluation - Pouyioutas, Philippos; Zantides, Evripides; Poveda, Maria; Papadema, Aspasia (My University, 2009)
© 2009 IADIS. In this paper we present the University of Nicosia intranet and some design considerations regarding its interface. The intranet has been developed using the prototype approach of system development. Due to time constraints and the need to have it on-line as soon as possible, little consideration was given to the design aspects of its interface. The emphasis was placed on the rapid deployment of the system and on the functionality provided to the users. Once the system was released, we sought the expert advice of faculty of the Design Department of the University in order to improve its interface. Herein, we present the evaluation of the intranet's interface, address the interface's limitations and suggest specific improvements.
Keywords: Recommender systems; Education; Learning environment